2009
DOI: 10.1142/s012918310901400x
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Properties of an Evolving Network Model With Aging Mechanism

Abstract: In this paper, a growing network model with aging mechanism is investigated. Each new node of the network gets attached to the ith existing node with the probability ∼ k β i (t)e −ατ i , where k i is the degree of the ith node and τ i is its age at time t. β denotes attraction factor and α represents aging intensity. It is found that the network shows scaling behaviors such as scale-free and exponential distribution of degree. Moreover, the phase diagram in the β − α plane is observed, in which there are three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…To study the effect of this phenomenon on network evolution, the BA model has been modified by incorporating time dependence in the network. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Dorogovtsev and Mendes studied the case when the connection probability of the new node with an old one is not only proportional to the degree k but also to a power of its present age τ −α (τ is the age of a node). [10] They found that the network shows scale-free (SF) behavior only in the region α < 1.…”
Section: Introductionmentioning
confidence: 99%
“…To study the effect of this phenomenon on network evolution, the BA model has been modified by incorporating time dependence in the network. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Dorogovtsev and Mendes studied the case when the connection probability of the new node with an old one is not only proportional to the degree k but also to a power of its present age τ −α (τ is the age of a node). [10] They found that the network shows scale-free (SF) behavior only in the region α < 1.…”
Section: Introductionmentioning
confidence: 99%